Tanggapan Siswa Terhadap Model Pebelajaran Inkuiri Terbimbing pada Materi Fotosintesis di SMP Negeri 8 Banda Aceh - Nursafiah , (Universitas Islam Negeri Ar-Raniry, 2015)
This research aims to find out students' responses toward guided inquiry learning model. The method used is pre-experimental design. The population of this research were 165 students of class VIII SMP Negeri 8 Banda Aceh. The research subjects were 24 students of class VIII-4. The data were collected by using questionnaires and then analyzed descriptively by calculating the average of each aspect. Likert Scale questionnaire was converted into a quantitative scale. The statements in the questionnaires were consisted of positive and negative statements. The questionnaires were given to the students after implementing guided inquiry model. The results showed that students responded positively to the model developed, indicated that guided inquiry learning model is very helpful and train students to work independently. It contributed to the process of critical thinking and help students to understand the photosynthesis concept.